0773 Sleep Disordered Breathing Based on Symptoms And RDI in Primary School Children with Implication for Prevalence. (27th April 2018) - Wada, H; Kimura, M; Tajima, T; Shirahama, R; Hayashi, T; Suzuki, Y; Suzuki, Y; Sato, S; Maruyama, K; Endo, M; Ikeda, A; Tanigawa, T
Abstract: Introduction: We previously investigated primary school students in Matsuyama, Japan, and found that the prevalence of sleep disordered breathing (SDB), based on sypmptoms (Gozal 2012), was 0.6% in total (Sakamoto N et al, SLEEP 2016). The aim of the present study is to elucidate the association between respiratory disturbance index (RDI) and symptom-based SDB in children with high-risk for SDB, and further to estimate the prevalence of SDB based on RDI. Methods: STUDY 1: A cross sectional study on whole primary school children in a city in Japan was conducted. A questionnaire, which included questions regarding variables: such as sex, grade, height, weight, adenotonsillar hypertrophy, was delivered to parents or guardians of all the children (n=26, 599) via the schools, and their responses were collected by teachers. STUDY 2: 808 primary school children, who were highly risky for SDB, were enrolled and underwent questionnnaires and home-based sleep study, which sensed airflow and gave RDI. The association between symptom-based SDB score and RDI was determined. Then, the prevalence of RDI-based SDB was estimated. All the statistic analyses were conducted, using SAS version 9.4 software. Results: SDB based on symptoms and that on RDI were significantly associated. The estimated prevalence of RDI-based SDB was mostly same between male and female students: prevalence of SDB defined as 5 ≤ RDI was 0.9% and 0.2% for male and female students, respectively, those as 2 ≤ RDI were 10.4% and 8.7%, and those as 1 ≤ RDI were 25.6% and 25.0%. The prevalence between male and female childrens were msotly same, probably because the effect of oestrogen was not strong yet at the age of 6 to 12 years old. These data confirmed our previous study (Wada H et al, SLEEP 2017 in Boston). Conclusion: The prevalences of RDI-based SDB were 1% (5 ≤RDI), 10% (2 ≤ RDI) and 25% (1 ≤ RDI), both in male and female students. Support (If Any):